Future Changes of the Antarctic Coastal Current as seen from a Downscaling Experiment - Santos, Marina Noro dos (2018)
Climate global models have contributed to the understanding of climate changes impacts on several Earth system processes. It is known that impacts on the ocean large scale circulation are considerably relevant. However, these models are not suitable to represent regional scale processes. Therefore, to evaluate the climate change impacts on small scale processes downscaling is necessary. This study was divided in two parts. The first part consists of evaluation and understanding of the behavior of the Southern Ocean circulation from a large scale perspective. For this, we used the ocean component (Parallel Ocean Program version 2 - POP2) of the National Center for Atmospheric Research Community Earth System Model version 1 (NCAR-CESM1.0). The second part aimed to evaluate the Antarctic Coastal Current (ACoC) in the Weddell Sea through high-resolution regional simulations with the Regional Ocean model System (ROMS) which were forced with results from NCAR Community Climate System Model version 3.0 (NCAR-CCSM3), an earlier version of NCAR-CESM1, experiments of the Intergovernmental Panel on Climate Change (IPCC) Assessment Report 4 (AR4). The first simulation was forced with 20th century historical scenario (ROMS-20C3M) and comprises the 1980 to 1999 period, whereas the second run considers the 21st century scenario A2 (ROMS-SRESA2) which comprises the 2021 to 2047 period. Results from CESM1-POP2 represents satisfactorily the large scale mean patterns and is in agreement with available data. The results show the limitation of these models to reproduce important features of the coastal region, which makes downscaling necessary to understanding smaller scale processes. The ACoC and its transport (≈ 22 Sv) were satisfactorily represented by regional simulations. From the 20th to 21st century projections, weakening of the ACoC transport was observed and shown to be mainly related with changes in the termohaline forcing.